Regional economics - Singh, Jiwitesh Kumar (Varanasi, 1978)
Regional economics is a relatively new branch of econo mics, but it is rapidly developing as an academic discipline which has excited an increasingly large amount of interest in recent years. Its development as an academic discipline has been accelerated by its policy implications, not only for loca tion of industry measures but also for regional and sub-regio nal planning. In the post-war period, the achievement of the goal of full employment and the development of new techni ques of economic analysis have facilitated the growth of regi onal economics as a separate and distinct branch of economics.
Keywords: Economic development